Conversion from English deeds system to Torrens system of title registration in Penang and Malacca: process and problems - Maidin, Ainul Jaria (IIUM Press, 2009)
This research was aimed at examining the process of converting the land administration system prevalent in Penang and Malacca to the Torrens System enforce in the rest of the Peninsular Malaysian states. The introduction of the Torrens system to the states of Penang and Malacca where the English deeds system was the system of land administration, despite the implementation of the Torrens system of land administration in all the other Malay states had to be made progressively. This is because until independence the land tenure system in the two states introduced by the British colonial masters remained unchanged. The research will examine the significant provisions of the National Land Code (Penang and Malacca) Titles Act 1963 that was enacted to facilitate the conversion process. Finally the research will identify what are the processes undertaken to facilitate the conversion and the problems or challenges faced by the land administration authorities in the course of conversion.